The Development of a Procedure Model for Improving Land Data Quality (Case Study at the Land Office of Tulang Bawang Regency) - Gusmartin, Popie Hagy; Abdulharis, Rizqi; Hernandi, Andri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Accurate and up-to-date land data is essential for effective planning, development, and decision/policy making by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. However, land data does not yet have full data accuracy and reliability, thus weakening the usefulness of the land data itself. This study aims to develop a procedural model to improve the quality of land data. This study began by conducting a data classification method, namely conducting a comprehensive inventory of data in the database and archives of land book documents along with measurement letters. Based on the inventory results, a data adjustment method was then done by aligning data between the database and the archives of land book documents and measurement letters. Finally, a method of improving the quality of land data (data quality improvement) was carried out by improving land data to be better. As a form of supervisory control/monitoring, data verification was carried out on data that had been improved using purposive sampling. The results of this study indicate that the systematic application of this method can produce land data with good data accuracy and reliability. Improving the quality of land data results in complete and accurate mapping, and higher data accuracy, although in one village statistically it has not shown positive data, but with the improvement in the quality of land data, it has increased the accuracy of high and detailed data, as well as increased transparency and accountability to the community.